Location optimization of silicon carbide foam packings in the unstirred packing trays reactor for the enhancement of solidified natural gas storage - Linqing, Tian; Ha, Li; Wang, Li; Chen, Guangjin; Coulon, Frederic; Jiang, Yuelu; Zeng, Xinyang; Zhang, Ruifeng; Wu, Guozhong (Elsevier, 2022)
Solidified natural gas technology shows significant potential for storing safely multi-fold volumes of natural gas in clathrate hydrates, but the main concern is the stochastic and slow process of hydrate nucleation making it unstable and unpredictable in practice. To overcome this limitation, methane hydrate was synthesized in a silicon carbide (SiC) ceramic foam packing trays reactor without stirring. Results suggested that the packing trays should be located near the gas-water interface instead of immersed in the aqueous phase, which decreased the induction time by about 98%. Results also highlighted the synergistic effects between the capillary wicking from the porous packings and the water suction from the initially formed hydrate clusters, which pumped water from the aqueous phase into the packings’ pores to provide an unsaturated porous environment for hydrate nucleation. It demonstrated that these two driving forces might also compete for water which became adverse to hydrate formation.
Keywords: methane hydrate; SiC foam tray; nucleation; solidified natural gas; gas storage